Prototype of the Strategy for the Development of HR Competencies in the State Civil Service in Barru Regency - Andi Rahmatiah Rasyid (Program Pascasarjana Universitas Negeri Makassar, 2020)
This study aims to develop a Human Resources competency strategy at the Barru Regent's Office. This research specifically focuses on the prototype design of Human Resources Development apparatus strategies that are effectively used by the Barru district government in the development of Human Resources apparatuses in order to perform high. This research uses a phenomenological approach, the main data collection techniques are interviews, observation Data analysis techniques used is a descriptive qualitative data analysis technique. The analysis was conducted after data collection through interviews and direct observation in the field. The results of the study include the development of quantity and quality of Human Resources Apparatus through mapping, Performance and Competency Mapping through internal policy mechanisms with the principles of Manage Human Performance, Maintenance planning, recruitment, career development, rewards, and dismissal, through Evaluation of Development Performance through training and Internal Guidance and External with the principles of Train, educate and Development and Negotioation for Work Conditions, Meeting the needs through recruitment, promotion and Mutation of the Recruit Activity principle.